Where My Girls At? A Critical Discourse Analysis of Gender, Race, Sexuality, Voice and Activism in Ottawa’s Capital Slam Poetry Scene - Tenn-Yuk, Jenna (Université d'Ottawa / University of Ottawa, 2014)
Ottawa’s Capital Slam poetry scene has transformed over the past decade, marking a shift in the identities, discourses and performance styles of local poets. This thesis investigates these changes and trends within the time periods of 2008-2010 and 2012- 2014. This thesis demonstrates the shift from male poets of colour in 2008-2010 to female voices in 2012-2014 at Capital Slam, through an examination of Ottawa’s history and a multimodal critical discourse analysis of online performances. In particular, the creation of local alternative poetry shows over the past five years has increased the representation of female poets and transformed the racial dynamics of the scene. During the period 2008-2010 and 2012-2014, poets used key historical elements of slam poetry such as storytelling and speaking through personal experiences to effectively demonstrate how marginalized individuals can speak counter-narratives to dominant culture. The use of storytelling allowed these poets to engage, connect and dialogue with the audience, as well as demonstrate their different identities, discourses and performance styles.
Keywords: Slam poetry; Spoken word; Poetry; Critical discourse analysis; Gender; Race; Sexuality; Voice; Ottawa; Capital Slam; Hip-hop